On the law, work and functioning of the EU agency for cybersecurity - Seatzu, Francesco; Carrillo Santarelli, Nicolás (PEACE & SECURITY-PAIX ET SÉCURITÉ INTERNATIONALES (EuroMediterranean Journal of International Law and International Relations), 2024)
The EU Cyber security Agency (carrying the acronym ENISA from its original name) is the main agency for the EU's cyber security programme. ENISA was initially created as an advisory body rather than as a traditional monitoring agency and its unique approach reflects the EU's shift towards a more regulatory approach to cyber security problem-solving. This study explores the role of ENISA in governance and presents the complex concept of observational memory “observation” from a critical Foucauldian perspective. ENISA's monitoring approach has allowed it to become a new form of management, with a model reminiscent of vision. This perspective has had a significant impact on the development of the EU cyber security regime and has challenged the traditional understanding of ENISA as an advisory body on cyber security issues. As the agency debates the balance between government and regulation, it continues to re-evaluate its role in the evolving cyber security landscape, forcing reflection on its success and events that shed light on cyber security issues.